EFFECTIVENESS OF USING SCRABBLE AS GAME-BASED LEARNING IN IMPROVING VOCABULARY AT CHILDREN - Romiza Ikbar (CV Grasta Glory, 2025)
This study aims to evaluate the effectiveness of Scrabble as a GBL (game-based learning) tool in improving English vocabulary mastery in 12-year-old children. Ten elementary school students living near the researcher's home participated in the study, which spanned one week and involved three meetings. The method used was quantitative, where data was collected through pre-tests and post-tests designed to measure students' vocabulary mastery, spelling accuracy, and their ability to form correct and meaningful English words. This study aims to evaluate the effectiveness of Scrabble as a game-based learning (GBL) tool for improving vocabulary mastery among 12-year-old EFL learners. A quantitative pre-experimental design was implemented over one week, consisting of three learning sessions involving ten elementary school students living near the researcher's home. We collected data using pre-tests and post-tests that measured vocabulary mastery, spelling accuracy, and the ability to construct meaningful English words. The results of the study showed a significant improvement after the intervention. In the pre-test, 70% of students scored below 60, indicating limited vocabulary mastery. After the intervention, all students scored above 60, with 50% achieving a score of 80 or higher and one student achieving the maximum score of 90. These findings suggest that Scrabble, when integrated with dictionary use, is not only enjoyable but also effective in improving vocabulary mastery and word comprehension in students. Future research should consider larger sample sizes and longer durations to examine the broader application of educational games in an EFL context.